Implementation Analysis of Total Sanitation Program Policy Community- Based (STBM) at the Health Office Jayawijaya District - Amos Andri Palulungan1, Indar1, Amran Razak1, Alwy Arifin, Nurhaedar Jafar, Syamsuddin (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Environments that have poor sanitary conditions can be a source of disease development. This clearly endangers the health of our society. The accumulation of garbage that cannot be managed properly, air, water and soil pollution can also be the cause. Efforts to protect the environment are the responsibility of all parties for this reason, awareness of all parties is needed. Based on statistical data, access to basic sanitation in Indonesia up to 2008 only reached 48.56%. One of the steps taken by the Government of Indonesia is by issuing the Decree of the Minister of Health of the Republic of Indonesia No. 3 of 2014 concerning STBM. The purpose of this study was to analyze the implementation of the STBM Program at the Jayawijaya District Health Office. The design of this study used a qualitative approach. Qualitative data was obtained by collecting data using triangulation techniques, namely in-depth interviews. In this research study, using the concept of implementation of George C. Edward II with four factors that influence the implementation of the Community-Based Total Sanitation Program. The results of this study indicate that the communication factor has been implemented but has not been maximized. The resource factor is still not available, both for the fulfillment of personnel and operational budgeting in implementing the program. As for the disposition factor, it looks quite high with the commitment of the program organizers. Meanwhile, the bureaucratic structure factor is based on a hierarchical organizational structure, but is not supported by related programs, and has not been accompanied by the development of Standard Operating Procedures for the implementation of the Community-Based Total Sanitation program. Communication and resources have not been maximized, so that facilitators should be trained regularly and increase staff in all Puskesmas in handling the STBM program. If the disposition is good, with a high commitment from the program organizers, while the bureaucratic structure is not working, then Standard Operating Procedures should be made.